1998
DOI: 10.1136/jmg.35.9.731
|View full text |Cite
|
Sign up to set email alerts
|

Family history of breast cancer: what do women understand and recall about their genetic risk?

Abstract: The current study has two aims: (1) to look at people's recall of risk information after genetic counselling and (2) to determine the impact ofreceiving an audiotape ofthe genetic consultation on level of recall, cancer related worry, and women's uptake of risk management methods.Using a prospective randomised controlled design, subjects receiving an audiotape were compared with a standard consultation group. Participants were drawn from attenders at the genetic clinics of two London hospitals and included 115… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
107
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 14 publications
13
107
2
Order By: Relevance
“…However, a single genetic counselling consultation may not be sufficient to shift these worries in some women and it might be unreasonable to expect otherwise. General levels of psychological morbidity (GHQ) remain unaffected by genetic counselling and are consistent with those previously reported elsewhere in the literature (Watson et al, 1998).…”
Section: Discussionsupporting
confidence: 78%
“…However, a single genetic counselling consultation may not be sufficient to shift these worries in some women and it might be unreasonable to expect otherwise. General levels of psychological morbidity (GHQ) remain unaffected by genetic counselling and are consistent with those previously reported elsewhere in the literature (Watson et al, 1998).…”
Section: Discussionsupporting
confidence: 78%
“…The discrepancies between two alternative ways of presenting that information may suggest a lack of clarity in the questions or difficulties with numerical notation. Communication of risk in the setting of a breast cancer family clinic is well recognised as a problem area, with no method of communication proven to achieve accurate understanding (Watson et al, 1998;Cull et al, 1999;Braithwaite et al, 2004;Lobb et al, 2005). Furthermore, the free text comments from a number of respondents showed that, despite scrupulous avoidance of the term 'low risk' in oral and written communications from the clinic, some feel inappropriately reassured, to the extent of believing their risk may be below that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Other measures Psychological distress and cancer worry were measured at baseline by the General Health Questionnaire (GHQ 30) (Goldberg and Williams, 1988) and the Cancer Worry Scale (Watson et al, 1998) as described by Fry et al (2003).…”
Section: Data Relating To the Consultationmentioning
confidence: 99%